An m6A methyltransferase confers host resistance by degrading viral proteins through ubiquitination - Jun Guo; Tianye Zhang; Haoxin Xie; Haichao Hu; Chaonan Shi; Yingjie Zhao; Jingliang Yin; Gecheng Xu; Zechi Wu; Pengkun Wang; Jiaqian Liu; Peng Liu; et al. (Nature Communications)
Abstract Posttranscriptional and posttranslational modifications play crucial roles in plant immunity. However, how plants fine-tune such modifications to activate antiviral immunity remains unknown. Here, we report that the m6A methyltransferase TaHAKAI is utilized by wheat yellow mosaic virus (WYMV) to increase viral genomic m6A modification and promote viral replication. However, TaHAKAI also functions as an E3 ligase that targets the viral RNA silencing suppressor P2 for degradation and inhibits viral infection. A major allele of TaHAKAI in a susceptible cultivar exhibited reduced E3 ligase activity but not m6A methyltransferase activity, promoting viral infection. Interestingly, TaHAKAIR attenuates the stability of TaWPS1 (Wheat paired spikelets 1, WPS1) mRNA, the negative regulator of spike development, which might increase panicle length and spikelet number by modulating its m6A modification. Our study reveals a mechanism for balancing disease resistance and yield by fine-tuning m6A modification and ubiquitination.